Bi65Cu13Ge41O6Br122, a low-valent compound of high structural complexity featuring the trigonal anion [O(GeIIBr2)3]2- with an sp2-Hybridized μ3-Oxide Ion - Gerisch, Alexander; Isaeva, Anna; Ruck, Michael (Zeitschrift für Anorganische und Allgemeine Chemie, 2013)
Thiny black air-sensitive crystals of Bi65Cu13Ge 41O6Br122 = (Bi5) 2(Bi9)6[O(GeBr2)3] 6[Cu6Ge5Br20][BiCu 7Ge18Br66] were obtained by very slow cooling of a melt of bismuth, bismuth tribromide, copper, and partly oxidized germanium. The crystal structure was described in the hexagonal space group P63 (no. 173) with a = 2584.2(4) pm and c = 1277.4(3) pm at 296(1) K. The polarity of the structure is subtle; large parts of the structure show a pseudo mirror plane. The highly diversified structure comprises five distinct structural fragments. For the first time, two polyhedral bismuth polycations, Bi 53+ (trigonal bipyramid, D3h) and Bi 95+ (tricapped trigonal prism, D3h), occur in one and the same chemical compound. A hitherto unknown group is the C 3h-symmetric μ3-oxido-tris[dibromidogermanate(II)] anion [O(GeBr2)3]2-, in which the germanium atoms of three GeIIBr2 units bind to a central oxide ion with sp2 hybridization. Density-functional-theory-based calculations on an isolated [O(GeBr2)3]2- anion confirm the stability of the group and its shape. Real-space chemical bonding analysis supports the polar nature of the Ge-O and Ge-Br bonds as well as the assigned oxidation states. The [O(GeBr2)3]2- anion and the bismuth polycations are embedded between two kinds of one-dimensional networks, which are running parallel to the c axis, a bromido-cuprate(I)- germanate(II) network 1∞[Cu6Ge 5Br20]4- and a bromido-bismuthate(III)- cuprate(I)-germanate(II) network 1∞[BiCu 7Ge18Br66]20-. The latter features pentacoordinate germanium(II) atoms with bond angles close to 90°. The solution of the crystal structure from X-ray diffraction data was hampered not only by severe pseudo-symmetry and the similar scattering power of copper, germanium, and bromine atoms, but also by substantial atomic disorder and orientational disorder of the Bi53+ polycation. Bi 65Cu13Ge41O6Br122 may be seen as a link between low-valent germanium compounds and low-valent bismuth compounds. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Bismuth; Germanium; Low-valent compounds; Polycations; Pseudosymmetry; sp